2009
DOI: 10.1177/0022034509338032
|View full text |Cite
|
Sign up to set email alerts
|

Localization of P. gingivalis in Preterm Delivery Placenta

Abstract: Increasing evidence suggests an association between periodontal disease and adverse pregnancy outcomes. Although infection is considered as a risk factor for preterm delivery, the localization of oral bacteria or their antigens in chorioamnionitis placental tissue has never been demonstrated. This study was devised to test the hypothesis that periodontal pathogens may be present and affect human placenta in cases of chorioamnionitis. Using immunocytochemistry, we have identified the presence of Porphyromonas g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 26 publications
6
142
0
4
Order By: Relevance
“…As a periodontal pathogen, P. gingivalis may indirectly contribute to adverse pregnancy outcomes (APO) by facilitating the release of bacterial products or inflammatory mediators into the maternal circulation that reach the maternal-fetal interface [2]. P. gingivalis could also directly promote APO via invasion and injury to utero-placental tissues; this is supported by several studies that have detected P. gingivalis DNA/antigen in the placenta, amniotic fluid, umbilical cord, and neonatal nasogastric aspirates from complicated pregnancies [3][4][5][6][7][8][9][10][11]. However, the significance of P. gingivalis as a causative agent of APO is sometimes viewed with skepticism due to several confounding factors.…”
Section: Introductionmentioning
confidence: 93%
“…As a periodontal pathogen, P. gingivalis may indirectly contribute to adverse pregnancy outcomes (APO) by facilitating the release of bacterial products or inflammatory mediators into the maternal circulation that reach the maternal-fetal interface [2]. P. gingivalis could also directly promote APO via invasion and injury to utero-placental tissues; this is supported by several studies that have detected P. gingivalis DNA/antigen in the placenta, amniotic fluid, umbilical cord, and neonatal nasogastric aspirates from complicated pregnancies [3][4][5][6][7][8][9][10][11]. However, the significance of P. gingivalis as a causative agent of APO is sometimes viewed with skepticism due to several confounding factors.…”
Section: Introductionmentioning
confidence: 93%
“…Analysis of the amniotic fluid shows the presence of periodontal pathogens like Eikenella [17], F.nucleatum, P. gingivalis [18,19]. These pathogenic bacteria induce cytokine formation, neutrophil activation, MMP synthesis which induces pre-term labor.…”
Section: Association Of Periodontal Health To Complications During Prmentioning
confidence: 99%
“…The pathologic mechanism of the periopathogen shows that it could infect syncytiotrophoblasts, chorionic trophoblasts, and amniotic epithelial cells [19] and promote inflammatory process through Toll like receptor 4. A case report of a stillbirth caused by F. nucleatum from the mother's mouth highlights the fact that an oral periodontal pathogen can, by hematologic pathway, colonize placenta and provoke fetal complications [20].…”
Section: Association Of Periodontal Health To Complications During Prmentioning
confidence: 99%
“…Katz et al (2009) observed that gram negative periodontopathogens get localised in the placenta resulting in chorioamnionitis, infected amniotic fluid or a fetal inflammatory response [16]. This has an adverse outcome on the gestational age as well as fetal growth.…”
Section: Discussionmentioning
confidence: 99%